Enrolment and Retention in Adult Basic Education Programs Some Theoretical Implications of a National Study Follow-up Study - Ellen Long (Adult Education Research Conference, 2001)
Using the findings of a national follow-up study (n=338), this paper discusses the factors associated with nonenrolment and dropping out of literacy and upgrading programs. In addition to illuminating the complexity of low enrolment and high drop out rates, the paper moves toward a more integrated understanding of the structural and agency-related explanations for these patterns.